Feather mites of the genus Passeroptes Fain (Acariformes: Dermationidae) from passerines (Aves: Passeriformes) of China - Mu, Ning; Kuang, Xi-Jun; Wang, Zi-Ying (Zootaxa, 2015)
Five new species of the feather mite genus Passeroptes (Acariformes: Dermationidae) are recorded from birds of the order Passeriformes in China: P. lioparis sp. nov. from Chrysotus chrysotis (Blyth) (Paradoxornithidae); P. motacillae sp. nov. from Motacilla cinerea Tunstall (Motacillidae); P. cyanodermae sp. nov. from Cyanoderma ruficeps Blyth (Timaliidae); P. periparus sp. nov. from Periparus ater (Linnaeus) (Paridae); P. aegithalos sp. nov. from Aegithalos iouschistos bonvaloti (Oustalet) (Aegithalidae).